Competition Policy and Black Empowerment: South Africa’s Path to Inclusion - Mncube, Liberty; Ratshisusu, Hardin (Southern Centre for Inequality Studies (SCIS), 2021)
Competition law is not just about the efficiency goal. Placing value on opportunities for black owned businesses to enter, expand, and participate in markets is likely to be a key element in South Africa’s route to become an efficient, competitive economic environment focused on development and ultimately benefiting all South Africans. The first democratic government of South Africa prioritised the transformation of society on a non-racial, democratic and local foundation. The expectation was that all law in South Africa would contribute to, amongst other things, economic transformation and redress the imbalances created by past racial divisions, and more important foster the participation of the previously marginalised people to participate in the mainstream economy. In South Africa, equity is a recognized goal and a permissible consideration of competition law and a key driver of inclusive markets, economic development and, ultimately, empowerment of black people.
Keywords: Competition law; Black owned businesses; Black Economic Empowerment; Competitive economic environmen